Description of Adolescent Level of Knowledge About the Impact of Early Marriage - Dian Farikasari; Erika Dewi Noorratri (Universitas Muhammadiyah Palu, 2023)
Early marriage is not a new phenomenon in Indonesia; it has been prevalent for a long time. Indonesia ranks fourth in the world for the highest number of early marriages, with approximately 1,220,900 girls under the age of 18 getting married in 2018. Based on data from the Central Bureau of Statistics (BPS), the percentage of early marriages in Central Java in 2021 was 21.78%, in Boyolali district in 2020 was 20.29%, and in Sambi sub-district, there were 28 cases of early marriages in 2022. Early marriages have both negative and positive impacts. The negative impacts of early marriages in Sambi sub-district include 28 individuals who have undergone early marriages, 5 pregnant individuals, 8 with a history of Neonatal complications, and 15 individuals who gave birth with a history of Low Birth Weight (LBW). The positive impact of early marriages is to avoid free association. Objective: To identify the level of knowledge among adolescent girls regarding the impacts of early marriages in Canden Village, Sambi Sub-district, Boyolali District. Method: This research is a quantitative descriptive study. The total number of respondents surveyed was 81. The level of knowledge was measured using a questionnaire instrument. The technique used was random sampling, and the study required a duration of 3 weeks. Results: The research findings indicate that the majority of adolescent girls in Canden Village have a moderate level of knowledge regarding the impacts of early marriages, with 43 individuals falling into the